Encyclopedia of early modern philosophy and the sciences - Jalobeanu, Dana; Wolfe, Charles T. (Springer, 2018)
Mechanical Philosophy -- Newtonianism -- Chemistry, Alchemy.-Language, Mind, and Logic -- Metaphysics and the Laws of Nature -- Methods of Reading, Writing, and Research -- Spaces for the Production of Knowledge, Practical Knowledge -- Aristotelianism and Late Scholasticism -- Emotions, Passions, and Mind -- Life Sciences: Medicine -- Life Sciences: Natural History -- Mechanics, Mixed Mathematics -- Natural Magic, Curiosity.-Experimental Philosophy -- Women in Philosophy and Science --